The quadruple and quintuple helix in innovation environments (incubators and science and technology parks) - Mineiro, Andrea Aparecida da Costa Mineiro (2021)
Purpose – The purpose of this paper is to investigate the literature on the representation of the quadruple andquintuple helix (QQH) in innovation environments such as incubators and science and technology parks (STPs).Design/methodology/approach – The authors used the integrative review as a methodologicalapproach and systematized studies regarding the main research objectives; theoretical approaches;methodology and study object; QQH representation, by identifying actor, performance and main results; andadditional contributions to the QQH model.Findings – As a result, the authors noticed a lack of standardization on the representation of the quadruplehelix, but the example of associations and community centers as representatives of the civil society. Thequintuple helix does not have an actor that represents the environment, but STPs foster sustainable actions,encourage the generation of green companies and stimulate sustainable practices among established companies.Originality/value – Based on changes in the economic and social scenarios, new theoretical approachesemerge to explain the innovation process, such as the QQH. Incubators and STPs are favorable settings forinteractions, according to the new models; however, there is a lack of studies addressing this topic in suchenvironments. Hence, this study contributes to understanding the existence and performance of QQH, byshowing how these new helices were identified, in addition to advancing the subject in innovationenvironments such as incubators and STPs.Keywords Ambientes de inovação, Hélice quadrupla, Hélice quíntupla, Incubadoras,Parques científicos e tecnologicos, Quadruple helix, Quintuple helix, Innovation habitats, Incubators,Science and technology parks.